Binder composition, sand composition, mold making kit and mold making method
A binder composition with water-soluble phenolic resin and amine compounds addresses formaldehyde generation and storage stability issues in mold making, ensuring reduced formaldehyde emission and enhanced mold strength.
Patent Information
- Application Number
- JP2023172514
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2042-12-21
AI Technical Summary
Existing mold making processes using alkaline phenolic resin generate formaldehyde, which worsens the working environment, and adding urea to reduce formaldehyde increases nitrogen content leading to casting defects and decreased mold strength, while resorcinol-based compositions have poor storage stability.
A binder composition containing water-soluble phenolic resin and amine compounds, such as primary, secondary, and polyvalent amines, with a pH of 12 or more, is used to capture formaldehyde, reducing its generation and maintaining mold strength, and the composition is formulated to have excellent storage stability.
The solution effectively reduces formaldehyde generation, maintains mold strength, and improves storage stability, minimizing nitrogen content and casting defects.
Smart Images

Figure 0007608555000001 
Figure 0007608555000002 
Figure 0007608555000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder composition, a sand composition, a kit for making a casting mold, and a method for making a casting mold. [Background technology]
[0002] One type of casting mold process is an alkaline phenol resin process using an alkaline phenol resin as a binder. A representative alkaline phenol resin process is a process in which an alkaline phenol resin and an organic ester as a hardener are added to a refractory granular material such as silica sand, and the mixture is kneaded to form a sand composition (mixed sand), and the obtained sand composition is filled into a wooden mold, a resin mold, a metal mold, or the like (hereinafter, these are also collectively referred to as "molds for casting") to form a mold, and the alkaline phenol resin is hardened to bind and solidify the refractory granular material to form a mold (self-hardening mold) (self-hardening mold forming method). Another known process is a process in which an alkaline phenol resin is added to a refractory granular material to form a sand composition, and the obtained sand composition is filled into a mold for casting to form a mold, and an organic ester or carbon dioxide gas as a hardener is passed through the sand composition to harden the alkaline phenol resin, thereby binding and solidifying the sand to form a mold (gas-hardening mold) (gas-hardening mold forming method).
[0003] However, formaldehyde is generated when the binder hardens, which can deteriorate the working environment. Conventionally, a method for reducing the amount of formaldehyde generated has been known in which a formaldehyde scavenger such as urea or resorcin is added to a binder. For example, Patent Document 1 discloses a method for producing a casting mold by filling a mold with mixed sand obtained by kneading a hardener composition containing a phenolic compound monomer such as resorcin and an organic ester, a fire-resistant granular material, and a water-soluble phenolic resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 2504660 Summary of the Invention [Problem to be solved by the invention]
[0005] However, when urea is added to the binder, a large amount of urea must be added in order to sufficiently reduce the amount of formaldehyde generated. As a result, the amount of nitrogen derived from urea in the binder composition increases, which may cause casting defects. In addition, since formaldehyde itself acts as a crosslinking agent, if urea captures formaldehyde, it becomes difficult to obtain the effect as a crosslinking agent, which reduces the strength of the mold.
[0006] On the other hand, since resorcinol is a type of phenolic resin, it captures formaldehyde and is incorporated into the hardening binder, so the strength of the mold can be maintained even if formaldehyde is captured by resorcinol. However, a binder composition containing resorcinol is likely to thicken and its storage stability is likely to decrease.
[0007] An object of the present invention is to provide a binder composition, a sand composition, a mold making kit, and a method for making a mold, which can reduce the amount of formaldehyde generated while maintaining mold strength and have excellent storage stability. [Means for solving the problem]
[0008] The present invention has the following aspects. [1] A water-soluble phenolic resin; One or more amine compounds selected from the group consisting of primary amines, secondary amines, and polyamines (excluding urea); Including, The binder composition, wherein the pH of an aqueous solution of the water-soluble phenolic resin at a concentration of 45% by mass at 25° C. is 12 or more. [2] The binder composition according to [1] above, wherein the content of the amine compound is 0.05 to 0.53 parts by mass, calculated as nitrogen, per 100 parts by mass of the water-soluble phenolic resin. [3] A sand composition comprising the binder composition according to [1] or [2] above and a refractory granular material. [4] The sand composition of [3], further comprising an organic ester. [5] A mold-making kit comprising the binder composition according to [1] or [2] above and a refractory granular material, each of which is independently selected from the group consisting of refractory granular material and refractory granular material. [6] The mold-making kit according to [5] above, further independently comprising one or more hardeners selected from the group consisting of organic esters and carbon dioxide gas. [7] A method for producing a mold, comprising filling the sand composition according to [4] above into a mold for producing a mold, and hardening the binder composition contained in the sand composition. [8] A method for producing a mold, comprising filling the sand composition according to [3] above into a mold for producing a mold, and passing an organic ester or carbon dioxide gas through the sand composition to harden the binder composition contained in the sand composition. Effect of the Invention
[0009] According to the present invention, it is possible to provide a binder composition, a sand composition, a mold making kit, and a method for making a mold, which can reduce the amount of formaldehyde generated while maintaining mold strength and have excellent storage stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The following describes in detail the forms for implementing the present invention, but the present invention is not limited to the embodiments described below, and various modifications are possible without departing from the gist of the present invention. In this specification and claims, a numerical range expressed by "to" means a numerical range including the numerical values before and after "to" as the lower and upper limits. In the following description, the term "mold" refers to a mold produced using the binder composition, the sand composition, or the mold-making kit of the present invention.
[0011] [Binding agent composition] Hereinafter, one embodiment of the binder composition according to the first aspect of the present invention will be described. The binder composition of the present embodiment contains the following water-soluble phenolic resin and amine compound (excluding urea). The binder composition may further contain, in addition to the water-soluble phenolic resin and the amine compound, other components (hereinafter also referred to as "optional components") as necessary, so long as the effects of the present invention are not impaired.
[0012] <Water-soluble phenolic resin> The pH of the water-soluble phenolic resin at 25° C. is 12 or more, preferably 12 to 14, and more preferably 12 to 13. In other words, the water-soluble phenolic resin contained in the binder composition of the present embodiment can be said to be an alkaline phenolic resin. The pH of the water-soluble phenolic resin is a value measured at a measurement temperature of 25° C. of the pH of an aqueous solution prepared by dissolving the water-soluble phenolic resin in water to a concentration of 45% by mass.
[0013] The water-soluble phenolic resin can be obtained by reacting one or more compounds selected from the group consisting of phenols and bisphenols (hereinafter referred to as "phenolic compounds") with aldehydes in an aqueous system in the presence of an alkali metal hydroxide by a conventional method. The water-soluble phenolic resin may be used alone or in combination of two or more kinds.
[0014] Examples of phenols include phenol, o-cresol, m-cresol, p-cresol, 2,3-xylenol, 3,5-xylenol, m-ethylphenol, m-propylphenol, m-butylphenol, p-butylphenol, o-butylphenol, resorcinol, hydroquinone, catechol, 3-methoxyphenol, 4-methoxyphenol, 3-methylcatechol, 4-methylcatechol, methylhydroquinone, 2-methylresorcinol, 2,3-dimethylhydroquinone, 2,5-dimethylresorcinol, 2-ethoxyphenol, 4-ethoxyphenol, 4-ethylresorcinol, 3-ethoxy-4-methoxyphenol, 2-propenylphenol, 2-isopropylphenol, 3-isopropylphenol, 4-isopropylphenol, 3,4,5-trimethylphenol, 2-isopropoxyphenol, 4-propoxyphenol, 2-allylphenol, 3,4,5-trimethoxyphenol, phenol, 4-isopropyl-3-methylphenol, pyrogallol, phloroglucinol, 1,2,4-benzenetriol, 5-isopropyl-3-methylphenol, 4-butoxyphenol, 4-t-butylcatechol, t-butylhydroquinone, 4-t-pentylphenol, 2-t-butyl-5-methylphenol, 2-phenylphenol, 3-phenylphenol, 4-phenylphenol, 3-phenoxyphenol, 4-phenoxyphenol, 4-hexyloxyphenol, 4-hexanoylresorcinol, 3,5-diisopropylcatechol, 4-hexylresorcinol, 4-heptyloxyphenol, 3,5-di-t-butylphenol, 3,5-di-t-butylcatechol, 2,5-di-t-butylhydroquinone, di-sec-butylphenol, 4-cumylphenol, nonylphenol, 2-cyclopentylphenol, 4-cyclopentylphenol, bisphenol A, bisphenol F, and the like. These phenols may be used alone or in combination of two or more.
[0015] Examples of bisphenols include bisphenol A, bisphenol F, bisphenol C, bisphenol S, and bisphenol Z. These bisphenols may be used alone or in combination of two or more.
[0016] Examples of aldehydes include formaldehyde, trioxane, furfural, paraformaldehyde, benzaldehyde, methylhemiformal, ethylhemiformal, propylhemiformal, salicylaldehyde, glyoxal, butylhemiformal, phenylhemiformal, acetaldehyde, propylaldehyde, phenylacetaldehyde, α-phenylpropylaldehyde, β-phenylpropylaldehyde, and the like. Examples of suitable benzaldehyde derivatives include o-hydroxybenzaldehyde, m-hydroxybenzaldehyde, p-hydroxybenzaldehyde, o-chlorobenzaldehyde, o-nitrobenzaldehyde, m-nitrobenzaldehyde, p-nitrobenzaldehyde, o-methylbenzaldehyde, m-methylbenzaldehyde, p-methylbenzaldehyde, p-ethylbenzaldehyde, and p-n-butylbenzaldehyde. These aldehydes may be used alone or in combination of two or more.
[0017] As the phenol-based compound, either one of phenols and bisphenols may be used alone, or a mixture of phenols and bisphenols may be used.
[0018] Examples of the hydroxide of an alkali metal include sodium hydroxide, potassium hydroxide, lithium hydroxide, etc. Among these, sodium hydroxide and potassium hydroxide are preferred. These alkali metal hydroxides may be used alone or in combination of two or more.
[0019] When the phenolic compound is reacted with the aldehyde, a monomer capable of condensing with the aldehyde (such as urea, cyclohexanone, melamine, etc.) may be added to the reaction system. The resulting alkaline phenol resin may be diluted with water or a monohydric alcohol (eg, methanol, ethanol, propanol, etc.) to a desired concentration.
[0020] The water-soluble phenolic resin can be used in a state containing water or a solvent such as an organic solvent. The water content (moisture content) relative to the total mass of the water-soluble phenolic resin is not particularly limited, but is preferably 30 to 80 mass%, more preferably 40 to 70 mass%. If the water content is 30 mass% or more, uneven kneading due to high viscosity is unlikely to occur. If the water content is 80 mass% or less, a mold with high strength is likely to be obtained.
[0021] The content of the water-soluble phenolic resin is preferably 35 to 65 mass %, more preferably 40 to 60 mass %, and even more preferably 45 to 50 mass %, based on the total mass of the binder composition. When the content of the water-soluble phenolic resin is equal to or more than the lower limit, sufficient binding properties are obtained and the hardening speed of the binder composition is increased. When the content of the water-soluble phenolic resin is equal to or less than the upper limit, an increase in the viscosity of the binder composition can be suppressed. In addition, the strength of the mold is improved. In this specification, the "content of the water-soluble phenolic resin" is a pure content. In other words, when the water-soluble phenolic resin contains a solvent, it is the mass obtained by subtracting the total content of the solvent from the total mass of the water-soluble phenolic resin.
[0022] <Amine compounds> The amine compound is at least one selected from the group consisting of primary amines, secondary amines and polyamines (excluding urea). These amine compounds may be used alone or in combination of two or more.
[0023] Examples of primary amines include linear primary amines such as monomethylamine, monoethylamine, monopropylamine, monomethanolamine, and monoethanolamine, cyclic primary amines such as aniline, toluidine, and phenylethylamine, and amino acids such as glycine. Among these, monoethylamine, monoethanolamine, and glycine are preferred, and monoethanolamine is more preferred. These primary amines may be used alone or in combination of two or more.
[0024] Examples of secondary amines include chain secondary amines such as dimethylamine, diethylamine, dipropylamine, ethylmethylamine, dimethanolamine, and diethanolamine, and cyclic secondary amines such as diphenylamine and pyridine. Among these, dimethanolamine is preferred. These secondary amines may be used alone or in combination of two or more.
[0025] Examples of the polyamine include chain polyamines such as ethylenediamine and diethyltriamine, and cyclic polyamines such as piperazine, melamine and benzoguanamine. Among these, ethylenediamine and piperazine are preferred. These polyamines may be used alone or in combination of two or more.
[0026] The content of the amine compound is preferably 0.10 parts by mass or more, more preferably 0.20 parts by mass or more, even more preferably 0.30 parts by mass or more, and particularly preferably 0.40 parts by mass or more, relative to 100 parts by mass of the water-soluble phenolic resin. The content of the amine compound is preferably 1.18 parts by mass or less, more preferably 1.00 parts by mass or less, even more preferably 0.70 parts by mass or less, and particularly preferably 0.50 parts by mass or less, relative to 100 parts by mass of the water-soluble phenolic resin. If the content of the amine compound is the above lower limit or more, the amount of formaldehyde generated can be further reduced. If the content of the amine compound is the above upper limit or less, the strength of the mold can be well maintained. The upper and lower limits of the content of the amine compound can be arbitrarily combined. For example, the content of the amine compound is preferably 0.10 to 1.18 parts by mass, more preferably 0.20 to 1.00 parts by mass, further preferably 0.30 to 0.70 parts by mass, and particularly preferably 0.40 to 0.50 parts by mass, relative to 100 parts by mass of the water-soluble phenolic resin. In the present invention, "100 parts by mass of the water-soluble phenolic resin" is the amount calculated as the pure content.
[0027] The content of the amine compound is preferably 0.05 parts by mass or more, more preferably 0.06 parts by mass or more, even more preferably 0.07 parts by mass or more, and particularly preferably 0.09 parts by mass, relative to 100 parts by mass of the water-soluble phenolic resin, in terms of nitrogen. The content of the amine compound is preferably 0.53 parts by mass or less, more preferably 0.40 parts by mass or less, even more preferably 0.30 parts by mass or less, and particularly preferably 0.20 parts by mass or less, relative to 100 parts by mass of the water-soluble phenolic resin, in terms of nitrogen. If the content of the amine compound is equal to or more than the lower limit, the amount of formaldehyde generated can be further reduced. If the content of the amine compound is equal to or less than the upper limit, the strength of the mold can be well maintained. The upper and lower limits of the content of the amine compound can be arbitrarily combined. For example, the content of the amine compound is preferably 0.05 to 0.53 parts by mass, more preferably 0.06 to 0.40 parts by mass, further preferably 0.07 to 0.30 parts by mass, and particularly preferably 0.09 to 0.20 parts by mass, relative to 100 parts by mass of the water-soluble phenolic resin, calculated as nitrogen.
[0028] The content of the amine compound in terms of nitrogen can be calculated based on the content of the amine compound relative to 100 parts by mass of the water-soluble phenolic resin, the molecular weight of the amine compound, and the number of nitrogen atoms per molecule, according to the following formula (i). Amine compound content in nitrogen equivalent = (amine compound content / amine compound molecular weight) × 14.0 × number of nitrogen atoms (i)
[0029] <Optional ingredients> Examples of the optional components include a silane coupling agent, water, and solvents such as organic solvents. Examples of the organic solvent include methanol. If the binder composition contains a silane coupling agent, the strength of the mold is further improved. Examples of the silane coupling agent include N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-glycidoxypropyltriethoxysilane.
[0030] The binder composition may contain a formaldehyde scavenger other than the above-mentioned amine compound (hereinafter, also referred to as "other formaldehyde scavengers") within a range that does not impair the effects of the present invention. However, since the binder composition of the present embodiment can sufficiently reduce the amount of formaldehyde generated without containing other formaldehyde scavengers, it is not necessary to contain other formaldehyde scavengers. In consideration of mold strength, mold manufacturing costs, quality of cast products, and the like, it is preferable that the binder composition does not substantially contain other formaldehyde scavengers. Here, the term "substantially free" means that, except for those unintentionally contained, other formaldehyde scavengers are not intentionally added to the binder composition. Other formaldehyde scavengers include, for example, urea, resorcinol, pyrogallol, and the like.
[0031] <Manufacturing method> The binder composition can be obtained by mixing a water-soluble phenolic resin and an amine compound, and, if necessary, optional components. When the binder composition contains an optional component, the optional component may be added in advance to the water-soluble phenolic resin.
[0032] <Action and effect> The binder composition of the present embodiment described above contains the above-mentioned amine compound, so even if formaldehyde is generated during curing of the binder composition, the generated formaldehyde can be captured. This is thought to be because, as shown in the following reaction formula, for example, the water-soluble phenolic resin reacts with the formaldehyde and the amine compound (Mannich reaction), and the formaldehyde is taken into the reaction product. Note that the reaction formula shown below is a reaction formula when the water-soluble phenolic resin is an alkali resol resin and the amine compound is monoethanolamine.
[0033] [ka]
[0034] As described above, the formaldehyde is incorporated into the reaction product. That is, the hardening reaction proceeds while the formaldehyde is being incorporated into the water-soluble phenolic resin, so that the strength of the mold can be maintained. In addition, the binder composition containing the amine compound is less likely to thicken, and therefore has excellent storage stability. In addition, since amine compounds are cheaper than resorcinol, the manufacturing cost of the mold can be reduced.
[0035] However, if the binder composition contains a large amount of nitrogen atoms, the resulting mold will also contain a large amount of nitrogen atoms. If such a mold is used to produce a casting, a gas defect (casting defect) called a pinhole may be induced. However, in the binder composition of the present embodiment, even a small amount of the amine compound can sufficiently reduce the amount of formaldehyde generated, so there is no need to mix an amine compound more than necessary. The smaller the content of the amine compound, the more the nitrogen atom content in the binder composition can be reduced, and the more gas defects in the final cast product can be suppressed.
[0036] [Sand composition] Hereinafter, one embodiment of the sand composition according to the second aspect of the present invention will be described. The sand composition of this embodiment comprises the binder composition of the first aspect of the invention described above and a refractory granular material. The sand composition may further comprise an organic ester. The sand composition may contain, in addition to the binder composition, the refractory granular material and the organic ester, further components other than these (hereinafter also referred to as "optional components"), as necessary, within a range that does not impair the effects of the present invention.
[0037] <Fire-resistant granular material> As the refractory granular material, conventionally known natural sands such as silica sand, chromite sand, zircon sand, olivine sand, amorphous silica, alumina sand, and mullite sand; artificial sand, etc., can be used. In addition, used refractory granular materials that have been recovered (recovered sand) or regenerated (regenerated sand) can also be used. From the viewpoint of production costs, natural sand is preferred, and silica sand is more preferred. Artificial sand is preferred from the viewpoint of resistance to expansion due to heat. Taking into consideration the balance between production costs and heat resistance, natural sand and artificial sand may be mixed and used. These refractory granular materials may be used alone or in combination of two or more.
[0038] The average particle size of the refractory granular material is preferably 50 to 600 μm, more preferably 100 to 550 μm, and even more preferably 200 to 500 μm. If the average particle size of the refractory granular material is equal to or greater than the above lower limit, a mold with high strength can be obtained. If the average particle size of the refractory granular material is equal to or less than the above upper limit, the surface quality of the casting cast using the mold is excellent. The average particle size of the refractory granular material is the particle size (median size) corresponding to a cumulative frequency of 50% based on the volume distribution of the refractory granular material measured by dynamic light scattering.
[0039] <Binding agent composition> The content of the binder composition is preferably 0.5 to 3.0 parts by mass, more preferably 0.8 to 2.0 parts by mass, and even more preferably 1.0 to 1.5 parts by mass, based on 100 parts by mass of the refractory granular material. If the content of the binder composition is equal to or more than the above lower limit, a mold having higher strength is likely to be obtained. If the content of the binder composition is equal to or less than the above upper limit, uneven kneading is unlikely to occur. In this specification, the "content of the binder composition" is a net content. In other words, when the binder composition contains a solvent, it is the mass obtained by subtracting the total content of the solvent from the total mass of the binder composition.
[0040] <Organic ester> The organic ester contained in the sand composition of the present embodiment is in liquid form. As the liquid organic ester, those used as curing agents for alkaline phenol resins can be used, such as methyl formate, ethyl formate, propylene carbonate, monoacetin, diacetin, triacetin, ethylene glycol monoacetate, ethylene glycol diacetate, γ-butyrolactone, propiolactone, and ε-caprolactone. These liquid organic esters may be used alone or in combination of two or more.
[0041] The content of the organic ester is preferably 0.1 to 0.6 parts by mass, more preferably 0.16 to 0.4 parts by mass, and even more preferably 0.2 to 0.3 parts by mass, based on 100 parts by mass of the refractory granular material. When the content of the organic ester is equal to or more than the lower limit, the binder composition can be sufficiently hardened. When the content of the organic ester is equal to or less than the upper limit, the amount of gas generated during pouring due to an excessive content can be suppressed.
[0042] <Optional ingredients> Examples of the optional components include the optional components exemplified above in the description of the binder composition according to the first embodiment of the present invention. The sand composition may contain other formaldehyde scavengers as long as the effects of the present invention are not impaired. However, since the binder composition contained in the sand composition can sufficiently reduce the amount of formaldehyde generated without containing other formaldehyde scavengers, the sand composition does not need to contain other formaldehyde scavengers. Considering the mold strength, the manufacturing cost of the mold, the quality of the cast product, etc., it is preferable that the sand composition does not substantially contain other formaldehyde scavengers.
[0043] <Manufacturing method> The sand composition is obtained by mixing the refractory granular material and the binder composition, optionally with the organic ester and one or more of the optional ingredients. In addition, when the sand composition contains an organic ester, it is preferable to mix the refractory granular material and the organic ester to obtain a mixture, and then add the binder composition and, if necessary, optional components to the obtained mixture and further mix them.
[0044] <Action and effect> The sand composition of the present embodiment described above contains the binder composition of the first aspect of the present invention, and therefore the amount of formaldehyde generated can be reduced. Furthermore, by using the sand composition of the present embodiment, a mold with practical strength can be manufactured.
[0045] [Mold making kit] Hereinafter, one embodiment of the mold making kit according to the third aspect of the present invention will be described. The mold making kit of this embodiment independently contains a refractory granular material and the binder composition of the first aspect of the present invention described above. The mold making kit may further independently contain a hardener as described below. Here, "independently possessed" means that each component is present without being mixed or in contact with each other. Each component is first mixed or in contact with each other when the mold making kit is used. The mold making kit may be, for example, a collection of containers each containing a separate component.
[0046] The refractory granular material contained in the foundry mold making kit may be any of the refractory granular materials exemplified above in the explanation of the sand composition according to the second embodiment of the present invention.
[0047] The hardener contained in the mold making kit is one selected from the group consisting of organic esters and carbon dioxide gas. The organic ester contained in the mold making kit may be in liquid or gaseous form. Examples of the liquid organic ester include the liquid organic esters exemplified above in the explanation of the sand composition according to the second embodiment of the present invention. The gaseous organic ester may be a gasified liquid organic ester. Among these, methyl formate gas obtained by gasifying methyl formate and ethyl formate gas obtained by gasifying ethyl formate are preferable. These gaseous organic esters may be used alone or in combination of two or more.
[0048] When the mold making kit is an assembly of containers each containing each component separately, at least one of the container containing the refractory granular material and the container containing the binder composition may contain optional components, and preferably these containers are substantially free of other formaldehyde scavengers. Examples of the optional components include the optional components exemplified above in the description of the binder composition according to the first embodiment of the present invention.
[0049] [Mold manufacturing method] The method for producing a mold according to the fourth embodiment of the present invention is a method for producing a mold by a self-hardening mold making method. The fifth aspect of the method for producing a casting mold of the present invention is a method for producing a casting mold by a gas hardening casting molding method.
[0050] In the method for producing a casting mold of the fourth aspect of the present invention, the sand composition of the second aspect of the present invention containing an organic ester is filled into a mold for producing a casting mold (mold for casting), and the binder composition is hardened by the hardening action of the organic ester contained in the sand composition to produce the mold. A mold may be manufactured using the mold-making kit of the third aspect of the present invention. In this case, a refractory granular material, the binder composition of the first aspect of the present invention, a liquid organic ester, and optional components as necessary are mixed to prepare a sand composition, and the obtained sand composition is filled into a mold for mold-making. When the mold-making kit of the third aspect of the present invention independently contains a liquid organic ester, the organic ester constituting the mold-making kit may be used to prepare a sand composition.
[0051] In the method for producing a casting mold of the fifth aspect of the present invention, the sand composition of the second aspect of the present invention that does not contain an organic ester is filled into a mold for casting, and an organic ester or carbon dioxide gas is passed through to harden the binder composition contained in the sand composition by the hardening action of the organic ester or carbon dioxide gas, thereby producing a casting mold. A mold may be manufactured using the mold-making kit of the third aspect of the present invention. In this case, a refractory granular material, the binder composition of the first aspect of the present invention, and optional components, if necessary, are mixed to form a sand composition, and the resulting sand composition is filled into a mold for mold-making. When the mold-making kit of the third aspect of the present invention independently contains a gaseous organic ester or carbon dioxide gas, the organic ester or carbon dioxide gas constituting the mold-making kit may be used to aerate the sand composition in the mold for mold-making.
[0052] The flow rate of the organic ester or carbon dioxide gas is preferably 5 to 30 L per minute, more preferably 10 to 20 L. When the flow rate is equal to or higher than the lower limit, the binder composition is sufficiently cured. When the flow rate is equal to or lower than the upper limit, the room temperature strength of the mold can be well maintained. The time for aerating the organic ester or carbon dioxide gas (aeration time) is preferably 30 to 180 seconds, more preferably 60 to 180 seconds. If the aeration time is equal to or more than the lower limit, the binder composition is sufficiently cured, but if the aeration time exceeds the upper limit, the curing of the binder composition reaches a plateau, which simply increases the cost.
[0053] According to the method for manufacturing a mold of the present embodiment described above, a sand composition containing a refractory granular material and the binder composition of the first aspect of the present invention is used, so that the amount of formaldehyde generated can be reduced while maintaining the strength of the mold. EXAMPLES
[0054] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. The materials used in each example are shown below. Various measurement methods are also shown below. In the following examples, unless otherwise specified, "parts", "%" and "ppm" respectively indicate "parts by mass", "% by mass" and "ppm by mass". Working Example 2 ~9 is a reference example.
[0055] [Measurement and evaluation method] <Measurement of formaldehyde emissions> 30.0 g of the sand composition immediately after kneading was placed in a 1 L polyethylene container and stored for 1 hour under conditions of a temperature of 20° C. and a humidity of 50%. The amount of formaldehyde generated in the container after storage was measured using a Kitagawa gas detector.
[0056] <Compressive strength measurement> The compressive strength of the test pieces was measured using a bench-top compression tester (manufactured by Takachiho Kikai Co., Ltd.) in accordance with the JIS Z 2601 testing method for casting sand.
[0057] <Evaluation of storage stability> 1 kg of the binder composition immediately after preparation was placed in a 1 L polyethylene container and stored for 15 days under conditions of a temperature of 35°C and a humidity of 50%. The viscosity of each of the binder compositions before and after storage was measured at 25°C using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., product name "VISCOMETER TV-25"). The increase in viscosity of the binder composition after storage relative to the viscosity of the binder composition before storage was determined, and the storage stability of the binder composition was evaluated according to the following evaluation criteria. Good: Viscosity increase is less than 1.2 times. ×: Viscosity increase is 1.2 times or more.
[0058] <Calculation of nitrogen atom content> The nitrogen atom content in the binder composition was calculated based on the amounts of the various components used in the preparation of the binder composition, the molecular weight of the additive, and the number of nitrogen atoms per molecule according to the following formula (ii). The nitrogen atom content is the amount (ppm) relative to the total mass of the binder composition. Nitrogen atom content in binder composition=100×10,000×{(amount of additive mixed / molecular weight of additive)×atomic weight of nitrogen atom (14.0)}×number of nitrogen atoms / (total amount of water-soluble phenolic resin, additive, and water mixed) (ii)
[0059] [Synthesis of water-soluble phenolic resin] Into a 3 L four-neck flask equipped with a stirrer, a thermometer, an Allen condenser, and a dropping funnel, 364.9 g (3.69 mol) of phenol, 420.3 g (7.00 mol) of 50% formalin, 1.73 g (0.014 mol) of zinc carbonate, and 138.8 g of ion-exchanged water were added, and 104.1 g of 48% aqueous sodium hydroxide solution was further added. Next, a mantle heater was attached to the four-neck flask, and the internal temperature was raised to 90°C, and then the mixture was kept at 90°C for 2 hours. Next, 219.6g of ion-exchanged water was added, and after uniform mixing by stirring, 69.4g of 48% aqueous sodium hydroxide solution and 138.8g of 48% aqueous potassium hydroxide solution were added in sequence at a drop rate such that the liquid temperature was 45°C or less. Next, 10.4g of 3-glycidoxypropyltriethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name "Shin-Etsu Silicone MBE-403") was added as a silane coupling agent, and then 28.7g of ion-exchanged water was added to obtain 1487.6g of an alkali resol resin, which is a water-soluble phenolic resin. The water-soluble phenolic resin was dissolved in ion-exchanged water to prepare an aqueous solution having a purity of 45%. The pH of the aqueous solution was measured at 25° C. and found to be 12.5.
[0060] [Examples 1 to 9, Comparative Examples 1 to 5] <Preparation of Binder Composition> According to the formulations shown in Tables 1 to 3, the water-soluble phenolic resin, the additives, and the ion-exchanged water necessary for the content of the water-soluble phenolic resin in the binder composition to be 45% were mixed at 20°C until uniform, to obtain a binder composition. The amount of the water-soluble phenolic resin in the tables is the amount converted into a pure content. The amount of the solvent in the tables is the total amount of the solvent contained in the binder composition. The solvent includes the ion-exchanged water used in the preparation of the binder composition, as well as the solvent carried over from the raw materials used in the synthesis of the water-soluble phenolic resin. The nitrogen atom content in the resulting binder composition was determined. The binder compositions obtained in Example 2 and Comparative Examples 2 and 4 were evaluated for storage stability. The results are shown in Tables 1 and 3.
[0061] <Preparation of Sand Composition> According to the formulations shown in Tables 1 to 3, the fire-resistant granular material and an organic ester curing agent for alkaline phenolic resin (Alpha System Curing Agent "AH-530" manufactured by Gun-ei Chemical Industry Co., Ltd., a mixture of triacetin and ethylene glycol diacetate) were added to a Shinagawa-type universal mixer (manufactured by Shinagawa Kogyosho Co., Ltd., product name "MIXER") and mixed for 60 seconds. Next, according to the formulations shown in Tables 1 to 3, a binder composition was further added and mixed for 60 seconds to obtain a sand composition (mixed sand). The amounts in the tables are calculated as pure contents. The amount of formaldehyde generated from the obtained sand composition was measured. The results are shown in Tables 1 to 3. As the refractory granular material, natural sand or artificial sand was used. As the natural sand, silica sand (manufactured by Mitsubishi Corporation Construction Materials Co., Ltd., product name "Fremantle New Sand") or silica sand (recycled sand) was used. The artificial sand used was Alsand (manufactured by Ito Kiko Co., Ltd., "Alsand #1000").
[0062] <Preparation of test specimen> The sand composition was immediately filled into a wooden mold having a plurality of cylindrical shapes of 50 mm in diameter and 50 mm in depth under conditions of a temperature of 20°C and a humidity of 50%, and the binder composition was allowed to harden. After 1 hour had passed from the start of kneading, a test piece was removed from the wooden mold. The compressive strength of the test pieces was measured 1 hour, 2 hours, 3 hours, and 24 hours after the start of kneading. The results are shown in Tables 1 to 3.
[0063] [Table 1]
[0064] [Table 2]
[0065] [Table 3]
[0066] As is clear from Tables 1 to 3, the binder compositions obtained in each Example were able to reduce the amount of formaldehyde generated. The test pieces prepared using these binder compositions had high compressive strength. Furthermore, the binder composition obtained in Example 2 had excellent storage stability. The binder compositions obtained in the remaining Examples also had the same storage stability as Example 2. On the other hand, in the case of Comparative Example 1 in which no additive was used, formaldehyde was easily generated. In the case of Comparative Example 2, in which urea was used as an additive, in order to obtain the same degree of reduction effect in the amount of formaldehyde generated as in Examples 4 and 6, four times the amount of urea was required as the additive (monoethylamine or piperazine) used in Examples 4 and 6. In addition, the test pieces obtained in Comparative Example 2 had lower compressive strength than the test pieces obtained in Examples 4 and 6. In the case of Comparative Example 3, even though four times the amount of urea was used as the additive (monoethanolamine) used in Example 8, formaldehyde was easily generated. The binder composition obtained in Comparative Example 4, which contained resorcin as an additive, had poor storage stability. In the case of Comparative Example 5, in which a tertiary amine was used as the additive, formaldehyde was easily generated.
Claims
1. A water-soluble phenolic resin, Monoethanolamine, Including, A binder composition in which the pH of an aqueous solution of the water-soluble phenolic resin at a concentration of 45% by mass at 25° C. is 12 or more (excluding those in which the nitrogen content in the binder composition is 0.05 to 0.40% by mass).
2. A water-soluble phenolic resin, Monoethanolamine, Including, The binder composition has a pH of 12 or more at 25° C. in an aqueous solution of the water-soluble phenolic resin at a concentration of 45% by mass, The content of the water-soluble phenolic resin is 45 to 50% by mass based on the total mass of the binder composition, The binder composition has a monoethanolamine content of 0.0225 to 0.045% by mass, calculated as nitrogen, based on the total mass of the binder composition.
3. A sand composition comprising the binder composition of claim 1 or 2 and a refractory granular material.
4. 4. The sand composition of claim 3 further comprising an organic ester.
5. A foundry mold-making kit comprising the binder composition according to claim 1 or 2 and a refractory granular material, each of which is independently selected from the group consisting of refractory granular material and refractory granular material.
6. 6. The mold making kit according to claim 5, further independently comprising one or more hardeners selected from the group consisting of organic esters and carbon dioxide gas.
7. A method for producing a mold, comprising filling a mold for producing a mold with the sand composition according to claim 4 and hardening the binder composition contained in the sand composition.
8. A method for producing a mold, comprising filling a mold for producing a mold with the sand composition according to claim 3 and passing an organic ester or carbon dioxide gas through the mold to harden the binder composition contained in the sand composition.
Citation Information
Patent Citations
Coated sand composition having excellent collapsing property
JP1986037346A
Component of binding agent for gas hardening mold
JP2001314939A
Binder composition for mold molding
JP2016002550A
Binder composition for cast molding
JP2016020002A
Binder composition for forming mold
JP2020022996A
